An Underwater Acoustic Positioning Algorithm for Compact Arrays With Arbitrary Configuration - Sun, Dajun; Ding, Jie; Zheng, Cuie; Huang, Weimin (IEEE journal of selected topics in signal processing, 2019)
Acoustic positioning plays an important role in underwater sensors network (USN). Ultrashort baseline (USBL) is a common underwater localization technique applied in USNs. Traditional USBL arrays consisting of three or four elements usually have low positioning accuracy and low robustness. Although recent USBL positioning algorithms can be applicable to multi-element arrays, they also have low positioning accuracy and need complex processing. To improve positioning accuracy, we design an algorithm for a multi-element array with arbitrary configuration. In the proposed algorithm, the bearing is estimated by applying a group of linear equations. To test the positioning accuracy of the proposed algorithm, a two-dimensional pentagon array is studied as an example using both numerical and field data and another three-dimensional array is also investigated in the numerical analysis. Both the numerical and experimental results indicate that the proposed algorithm has more accurate positioning results under the circumstance that some elements in the array fail to work and simplifies the computational procedure.